2022
DOI: 10.1155/2022/4144073
|View full text |Cite|
|
Sign up to set email alerts
|

A Quantitative Analysis of Country Relations in Foreign Direct Investment

Abstract: According to Dunning’s eclectic theory, the location advantages play a key role in international investment mode choice, in which the country relations are important determinants. In some previous studies, the country relations and another bilateral factor, the country distance, are often confused, which can result in the inconsistency of conclusions. And excepting political factors, the economic dependence and other relations are insufficiently considered in the literature. This article makes a distinction be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Computational Intelligence and Neuroscience has retracted the article titled "A Quantitative Analysis of Country Relations in Foreign Direct Investment" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Computational Intelligence and Neuroscience has retracted the article titled "A Quantitative Analysis of Country Relations in Foreign Direct Investment" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
“…Computational Intelligence and Neuroscience has retracted the article titled “A Quantitative Analysis of Country Relations in Foreign Direct Investment” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%